The Identification of Lynch Syndrome in British Columbia - Carol M Cremin; Linlea Armstrong; Sharlene Gill; David Huntsman; Chris Bajdik (Canadian Journal of Gastroenterology)
OBJECTIVE: To determine the prevalence of Lynch syndrome mutations in a Canadian hereditary cancer clinic population, and to determine the effectiveness of the program’s referral criteria and testing algorithm.